Infecção experimental intravaginal de camundongos BALB/C com Campylobacter fetus subsp. venerealis - Jordana Almeida Santana (2012)
The bovine genital campylobacteriosis (BGC) is a venereal disease of great importance to the world's livestock. Despite its relevance, there is little information about its pathogenesis and animal immune response, which could be demonstrated by a model of experimental infection in a laboratory animal. The objective of this study was to infect BALB/c mice with Campylobacter fetus subsp. venerealis, intravaginally, and establish an animal model in which this microorganism can be studied. BALB/c mice were inoculated intravaginally with C. fetus subsp. venerealis and infection was assessed by 7 days. During this period, they were collected vaginal washes for carrying out culture and Direct Immunofluorescence (DIF) techniques to identify the bacteria. Every day, after euthanasia, the genital tracts were removed and subjected to Immunohistochemistry (IHC), Hematoxylin and Eosin (HE) and DIF of the vaginal tissue imprint in slide. It was observed that BALB/c mice are infected by C. fetus subsp. venerealis, intravaginally, at any stage of estrous cycle without the need of immunosuppression or estrous cycle modification, remaining in the vagina of these animals for up to 7 days after experimental inoculation, which allows conclude that the BALB/c mouse can be established as experimental infection model for studies about C. fetus subsp. venerealis